PENGARUH TEKNOLOGI PEMATAHAN DORMANSI SECARA FISIK DAN KIMIA TERHADAP KEMAMPUAN DAYA BERKECAMBAH BENIH AREN (Arengan pinnata) - Maulana Rizki Siregar; Mukhlis Mukhlis; Qorry Hilmiyah Harahap (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2016)
This study aims to determine the influence technology dormancy breaking physical and chemical analyzes of seed germination ability aren (Arenga pinnata). The research was conducted on land cultivation practices Faculty of Agriculture, University of Muhammadiyah South Tapanuli, Padangsidimpuan City, District Padangsidimpuan North,village of Batang Ayumi Julu, North Sumatra Province; ± altitude of 450 m above sea level. This study was conducted after the completionof the seminar proposal, which began in June to the month of August2016, using a randomized block design (RAK) 1 factorial with 8 treatments, each treatment was given three replications. The treatment consists of P0 = (Control), P1 = scarification, soaking water 30 minutes, P2 = scarification, soaking water 1 hour, P3 = scarification, oven 45oC 15 minutes, and water immersion 1 hour, P4 = scarification, soaking warm water ± 45oC 30 minutes, P5 = Immersion KNO 31% for 24 hours, P6 = Immersion HCl 1% for 24 hours, and P7 = Immersion 1% H2SO4 for 24 hours. The parameters measured were the increase of water content (%), germination rate (% / etmal), the long axis of the embryo (cm), a growing percentage of the roots (%)and germination (%). Results showed treatment technology dormancy breaking the physical and chemical significant effect on the increase of seed moisture content (%), speed of germination (% / etmal), the long axis of the embryo (cm), a growing percentage of the roots (%) and germination (%). The best treatment is contained in the chemical treatment P7 = Immersion H2SO4 1% for 24 hours, followed by physical treatment P4 = scarification, soaking warm water 45oC ± 30 minutes.Key words: palm seeds, dormancy breaking, physical and chemical.